Work-Based Learning in Rural America: Employer Participation in School-to-Work Programs and Apprenticeships - Gary Paul Green (Journal of Research in Rural Education, 2005)
Since the 1980s, many states have initiated institutional reforms designed to address perceived deficiencies in traditional schooling. Most of these reforms involve stronger linkages between employers and schools. In this article, I examine the factors influencing employer involvement in school-to-work programs and apprenticeships in rural America. Data are drawn from a telephone survey of a stratified random sample of 1,590 employers in nonmetropolitan areas of the U.S. Firm size is the strongest factor influencing employer involvement in school-to-work programs. Employers expressing difficulty in recruiting workers are more likely to be involved in school-to-work programs. There is considerable regional variation in employer involvement, with firms in the West and Midwest more likely to be engaged in these activities. Large firms in the manufacturing sector are most likely to be offering apprenticeships.